The organizational climate and its relationship to the professional compatibility of employees in the university services sector - Toufik BERGHOUTI; Soumia ALIOUA (Journal of North African Economies, 2025)
This study aimed to reveal the relationship between the organizational climate and the professional compatibility of employees in the university services sector. To achieve the objectives of the study, we relied on a sample of (83) employees at the University Services Directorate of Laghouat, using the professional compatibility questionnaire (Sami Khalil Fahjan, 2010) and the organizational climate questionnaire (Fouzia H'wayen, 2014). After statistical treatment, the study concluded the following results: The organizational climate among the study sample members is not appropriate, as all the averages are below the average. - The level of general professional compatibility among the study sample members is heading in the direction of good compatibility. - There is a positive correlation between the organizational climate and professional compatibility among the study sample members.